Genetic compatibility between Anopheles lesteri from Korea and Anopheles paraliae from Thailand. - Taai,K. (Fundacao Oswaldo Cruz, 2015)
To assess differentiation and relationships between Anopheles lesteri and Anopheles paraliae we established three and five iso-female lines of An. lesteri from Korea and An. paraliae from Thailand, respectively. These isolines were used to investigate the genetic relationships between the two taxa by crossing experiments and by comparing DNA sequences of ribosomal DNA second internal transcribed spacer (ITS2) and mitochondrial DNA cytochrome c oxidase subunit I (COI) and subunit II (COII). Results of reciprocal and F1-hybrid crosses between An. lesteri and An. paraliae indicated that they were compatible genetically producing viable progenies and complete synaptic salivary gland polytene chromosomes without inversion loops in all chromosome arms. The pairwise genetic distances of ITS2, COI and COII between these morphological species were 0.040, 0.007-0.017 and 0.008-0.011, respectively. The specific species status of An. paraliae in Thailand and/or other parts of the continent are discussed.